2020
DOI: 10.1029/2020jd032514
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an Atmospheric River Over Australia and the Southern Ocean: II. Microphysical Evolution

Abstract: An atmospheric river affecting Australia and the Southern Ocean on 28-29 January 2018 during the Southern Ocean Clouds, Radiation, Aerosol Transport Experimental Study (SOCRATES) is analyzed using nadir-pointing W-band cloud radar measurements and in situ microphysical measurements from a Gulfstream-V aircraft. The AR had a two-band structure, with the westernmost band associated with a cold frontal boundary. The bands were primarily stratiform with distinct radar bright banding. The microphysical evolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…Observations support the embedded occurrence of a variety of secondary ice formation processes in clouds over the Southern Ocean, which are otherwise dominated by supercooled water. These processes range from as-sociation with seeding of ice crystals from colder cloud levels that appears consistent with a rime splintering process (Finlon et al, 2020) to studies suggesting the vital importance of ice production via breakup following ice-ice collisions (Sotiropoulou et al, 2021;Young et al, 2019).…”
Section: Introductionmentioning
confidence: 69%
“…Observations support the embedded occurrence of a variety of secondary ice formation processes in clouds over the Southern Ocean, which are otherwise dominated by supercooled water. These processes range from as-sociation with seeding of ice crystals from colder cloud levels that appears consistent with a rime splintering process (Finlon et al, 2020) to studies suggesting the vital importance of ice production via breakup following ice-ice collisions (Sotiropoulou et al, 2021;Young et al, 2019).…”
Section: Introductionmentioning
confidence: 69%
“…Furthermore, Finlon et al. (2020) found observational evidence for the seeder‐feeder mechanism operating in an AR over the ocean south‐east of Australia. In accordance with Wratt et al.…”
Section: Resultsmentioning
confidence: 99%
“…A range of studies have recognized orographic enhancement of frontal precipitation due to either or both of the two named mechanisms (Browning et al, 1974;Carruthers & Choularton, 1983;Rotunno & Houze, 2007;Viale et al, 2013), including for New Zealand (Purdy & Austin, 2003;Purdy et al, 2005;Revell et al, 2002;Wratt et al, 2000). Furthermore, Finlon et al (2020) found observational evidence for the seeder-feeder mechanism operating in an AR over the ocean south-east of Australia. In accordance with Wratt et al (1996), we propose a combination of the seeder-feeder-mechanism and convective dynamics triggered by the release of conditional instability through uplift to be a potential driver of the large observed orographic rainfall enhancement and associated high ablation rates to the west of the Main Divide in the Southern Alps.…”
Section: Atmospheric Dynamics Above Brewster Glaciermentioning
confidence: 99%
“…Such localized regions of heterogeneity, associated with “pockets” of ice and mixed phase within large swaths of supercooled liquid, could be nucleating via heterogeneous nucleation. Recent work has highlighted the relatively sparse but present ice nucleating particles observed over this region (e.g., Finlon et al., 2020; McCluskey et al., 2018).…”
Section: Discussionmentioning
confidence: 99%